The Star , 12 Mei 2010 - Loh, Ivan (Star Publications, 2010)
Orang asli in the Upper Perak area are to be trained as professional boat operators or forest guides under measures planned by the state government to integrate them into the development of Royal Belum as a world-class eco-tourism spot.